Heterozygous carriage of the alpha1-antitrypsin Pi*Z variant increases the risk to develop liver cirrhosis. Issue 6 (1st August 2018) - Strnad, Pavel; Buch, Stephan; Hamesch, Karim; Fischer, Janett; Rosendahl, Jonas; Schmelz, Renate; Brueckner, Stefan; Brosch, Mario; Heimes, Carolin V; Woditsch, Vivien; Scholten, David; Nischalke, Hans Dieter; et al.
Abstract : Objective: Homozygous alpha1-antitrypsin (AAT) deficiency increases the risk for developing cirrhosis, whereas the relevance of heterozygous carriage remains unclear. Hence, we evaluated the impact of the two most relevant AAT variants ('Pi*Z' and 'Pi*S'), present in up to 10% of Caucasians, on subjects with non-alcoholic fatty liver disease (NAFLD) or alcohol misuse. Design: We analysed multicentric case–control cohorts consisting of 1184 people with biopsy-proven NAFLD and of 2462 people with chronic alcohol misuse, both cohorts comprising cases with cirrhosis and controls without cirrhosis. Genotyping for the Pi*Z and Pi*S variants was performed. Results: The Pi*Z variant presented in 13.8% of patients with cirrhotic NAFLD but only in 2.4% of counterparts without liver fibrosis (p<0.0001). Accordingly, the Pi*Z variant increased the risk of NAFLD subjects to develop cirrhosis (adjusted OR=7.3 (95% CI 2.2 to 24.8)). Likewise, the Pi*Z variant presented in 6.2% of alcohol misusers with cirrhosis but only in 2.2% of alcohol misusers without significant liver injury (p<0.0001). Correspondingly, alcohol misusers carrying the Pi*Z variant were prone to develop cirrhosis (adjusted OR=5.8 (95% CI 2.9 to 11.7)). In contrast, the Pi*S variant was not associated with NAFLD-related cirrhosis and only borderline with alcohol-related cirrhosis (adjusted OR=1.47 (95% CI 0.99 to 2.19)). Conclusion: The Pi*Z variant is the hitherto strongest single nucleotide polymorphism-based risk factor for cirrhosis in NAFLD and alcohol misuse, whereas the Pi*S variant confers only a weak risk in alcohol misusers. As 2%–4% of Caucasians are Pi*Z carriers, this finding should be considered in genetic counselling of affected individuals.